Crisponi/CISS1 syndrome: A case series. Issue 5 (24th January 2016) - Alhashem, Amal M.; Majeed–Saidan, Muhammad Ali; Ammari, Amer N.; Alrakaf, Maha S.; Nojoom, Maha; Maddirevula, Sateesh; Faqeih, Eissa; Alkuraya, Fowzan S.; Garne, Ester; Kurdi, Ahmad M.
Abstract : Crisponi/CISS1 syndrome (MIM#272430) is a rare autosomal recessive disease characterized by major feeding difficulties, camptodactyly, and anhidrosis in early childhood; and the subsequent development of paradoxical cold‐induced sweating and scoliosis later in life. The syndrome is caused by biallelic mutations in CRLF1 or, much less commonly, CLCF1 . Although genotype/phenotype correlation has been elusive, it has been suggested that the level of the mutant protein may correlate with the phenotypic severity. However, we show in this series of 12 patients from four families, all previously unpublished, that the homogeneity of the recently described c.983dupG (p.Ser328Argfs∗2) mutation in CRLF1 was associated with a highly variable degree of severity, and that the phenotype significantly overlaps with the recently described COG6 ‐related anhidrosis syndrome (MIM#615328). Another fifth previously unpublished family is also described with a novel mutation in CRLF1, c.605delC (p.Ala202Valfs*32). In Saudi Arabia the prevalence of the syndrome is probably underestimated due to the difficulty in making the diagnosis considering the complex phenotype with typical neonatal and evolutive features. © 2016 Wiley Periodicals, Inc.